2009
DOI: 10.1021/jm801449a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Substituted Methoxybenzoyl-aryl-thiazole as Novel Anticancer Agents: Synthesis, Biological Evaluation, and Structure−Activity Relationships

Abstract: A series of 4-substituted methoxylbenzoyl-aryl-thiazoles (SMART) have been discovered and synthesized as a result of structural modifications of the lead compound 2-arylthiazolidine-4-carboxylic acid amides (ATCAA). The antiproliferative activity of the SMART agents against melanoma and prostate cancer cells was improved from μM to low nM range compared with ATCAA series. The structure-activity relationship was discussed from modifications of "A", "B" "C" rings and the linker. Preliminary mechanism of action s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 23 publications
5
114
0
Order By: Relevance
“…More and more derivatives have been demonstrated to present obvious antimicrobial, antitumor, antifungal activity, etc. [34][35][36][37][38][39][40][41][42] Hence, as part of our agrochemistry program aimed at the search for novel natural product-oriented bioactive molecules, based on the aforementioned, we utilized blactam scaffold as prototype structural unit and planed for the incorporating natural gallic acid and azetidinone moieties in a single molecular scaffold (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…More and more derivatives have been demonstrated to present obvious antimicrobial, antitumor, antifungal activity, etc. [34][35][36][37][38][39][40][41][42] Hence, as part of our agrochemistry program aimed at the search for novel natural product-oriented bioactive molecules, based on the aforementioned, we utilized blactam scaffold as prototype structural unit and planed for the incorporating natural gallic acid and azetidinone moieties in a single molecular scaffold (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Their current importance is testified by their ubiquitousness in the fields of medicinal chemistry, material science and agrochemicals [1]. Imidazole-based compounds exhibit diverse biological activities anticancer [2][3][4][5] antibacterial [6,7], antitubercular [8,9], antifungal [10,11], antiviral [12][13][14], anticonvulsant [15][16][17] and antiparkinson's agents [18,19]. The [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Screening results from the National Cancer Institute (NCI-60 screening) for our lead compound, LY-1-100, indicated nanomolar antiproliferative activity for all the cancer cell lines tested. Preliminary mechanism of action studies on this series of compounds indicated that they may interact with microtubules (110). In vivo testing with melanoma tumors showed substantial growth inhibitory activity for this series of compounds.…”
Section: Introductionmentioning
confidence: 93%
“…In our ongoing efforts to search for small molecules as potential therapeutic agents for advanced melanoma, our team recently discovered a new series of thiazole analogs that showed very potent activity against melanoma cells in vitro (110). One of the best compounds in this series has an IC 50 value below 60 nM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation